Electrical response of mortar with different degrees of saturation and deicing salt solutions during freezing and thawing. (May 2015) - Farnam, Yaghoob; Todak, Heather; Spragg, Robert; Weiss, Jason
Abstract: This paper discusses a series of electrical measurements made on cementitious mortars containing water–NaCl solutions (0–23.3% concentration by mass) over temperatures in the range of 23 °C to −35 °C. Electrical impedance spectroscopy, acoustic emission, and thermal measurements were made during cooling and heating to detect phase changes and resulting damage. The influence of the degree of saturation (DOS) and NaCl solution concentrations are examined. Three phase changes were detected: (1) eutectic phase change (∼−24 °C), (2) ice/water phase change (∼−4 °C to −4 °C), and (3) chemical phase change (∼−4.5 °C to −5.5 °C). While the resistivity is highly dependent on changes in temperature, a drastic increase in resistivity is observed during freezing. Additionally, a comparison of specimens above and below the critical DOS (i.e., the DOS required for damage to occur) shows that resistivity measurements may able to be used to quantify damage.